Evaluation of the presence of reinfection in patients presenting to the emergency department with COVID-19 symptoms after recovery - Akça, Hatice Şeyma; Özdemır, Serdar; Tuncer Kara, Kevser (Ondokuz Mayis Universitesi, 2022)
This study aimed to evaluate COVID-19 reinfection in patients that presented to the emergency department with similar or different COVID-19 symptoms after recovery from the disease. This retrospective study included patients aged over 18 years presenting to the emergency department between January 1, 2021 and July 1, 2021, who had been previously diagnosed with COVID-19 and received treatment for the disease. Statistical analysis was performed using SPSS version 22.0.A total of 199 patients, 54.3% female, were included in the study. PCR positivity was present in 2.5% of the patients, and it was statistically significantly low(p<0.001). The most common symptom was fatigue (46.2%), and the least common symptom was loss of taste (3.0%). However, there was a statistically significant correlation between the loss of taste and smell and PCR positivity (p=0.024 and p=0.043, respectively). The logistic regression analysis revealed that the loss of taste and loss of smell alone did not have an effect on PCR positivity (p=0.848, 95% confidence interval: 0.005-71.83 and p=0.287, 95% confidence interval: 0.001-9.369). In the Covid-19 management and treatment guide, it is necessary to make changes in terms of symptoms for people who have had Covid-19 disease. © 2022 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: Covid-19 reinfection; Covid-19 symptoms; PCR